Crack Detection in Concrete Railway Sleeper - Ramesh, Shruthi; Chavan, Sonali; Kankani, Juhi; Joshi, Uday (International Journal of Computer Sciences and Engineering, 2025)
In India, railway transport occupies an important position in providing the needful transport infrastructure to assist needs of a rapidly growing economy. Even though India has one of the largest rail networks in the world, it has not reached the global level in terms of safety and reliability. The major problems which affect safety and reliability are the crack detection done of the structures. These cracks lead to derailments of the tracks which may cause damage to life and property. This paper proposes a solution to the problem of railway sleeper crack detection using various image processing techniques.